OPTIMIZING EVACUATION PLANNING FOR TSUNAMI MITIGATION IN PACITAN USING GEOGRAPHIC INFORMATION SYSTEM A case Study In Pacitan Distric, East Java, indonesia - , fitria nuraini sekarsih, Dr. rer.nat. Djati Mardiatno, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pacitan is one of the vulnerable cities to tsunami in Indonesia. The city center of Pacitan is surrounded by hills. If tsunami happens, the hills can be the safest place for evacuation and the first alternative of the evacuation escape for the people. Unfortunately, the Pacitanâs city also surrounded by two rivers, Teleng and Grindulu Rivers that make most of the evacuees are very dependent on the bridge. If the bridge collapses because of earthquake, it means the evacuees are trapped in the city. Besides the limited access to the hills and the limited evacuation time to go to the hills make the evacuation process cannot run optimally. The evacuees need another solution. It is called vertical evacuation. The final purpose of this research is to analyze the optimum evacuation planning for tsunami mitigation using GIS. In general, the research method consists of seven parts, they are (1) data preparation, (2) calculating covered area by horizontal and vertical evacuation method within limited evacuation time, (3) assessment of the risk of public building (it depends on the element at risk (building) and tsunami hazard), (4) building the evacuation coverage area for vacuation, (5) estimating the population number and density in day and night scenario, (6) analyzing capacity of the building based on the number of population and evacuation time. (7) giving recommendation. The result shows that ninety six percent people in Pacitan will run to the hills if tsunami happens. The evacuation site prepared by government, just cover the evacuees about 6.41% in the day or 9.93% at night by using minimum evacuation speed scenario. The simulation with maximum evacuation speed scenario covers about 27.47 % evacuees in the day and 29.17 % evacuees in the night. The limited network makes the coverage area is very limited. Horizontal evacuation method cannot run optimally with the exits facilities. Another method needs to be improved to cover the entire of the evacuees to save their lives. It is called âvertical evacuation method.â Total of the public building in the research area is about 350 buildings. The risk condition in this area with âvery lowâ class is 9.3 %, âlowâ is 3.4 %, âmediumâ is 2.9 %, âhighâ is 83.1 %, and âvery highâ is 1.4 %. By using the exits public building and its improvement, it can cover about 479 ha or it can cover 10,650 people by using worst case scenario. After the scenario, total of the evacuees who cannot get access to the shelter both in horizontal evacuation and vertical evacuation by using worst case scenario is 36,409 evacuees in day and 39,213 evacuees at night. The capacity of both of evacuation methods is very limited. Thus the evacuation processes need to be improved.